Biodegradability of antimicrobial edible films and coatings : what's the real thing? - Pérez, Leonardo Martín (2019)
Fil: Pérez, Leonardo Martín. Pontificia Universidad Católica Argentina. Facultad de Química e Ingeniería del Rosario; Argentina